Effects of trail and greenspace exposure on hospitalisations in a highly populated urban area: retrospective cohort study of the Houston Bayou Greenways program. Issue 3 (4th March 2023) - Simon-Friedt, Bridget R.; Pan, Alan P.; Nisar, Tariq; Al-Kindi, Sadeer; Nunley, Amanda; Graiff, Lisa; Kash, Bita A.; Maddock, Jay E.; Nasir, Khurram
ABSTRACT: Exposure to urban greenspaces has been linked to improved health outcomes for prevalent conditions. Studies have observed traditional block greenspaces, whereas linear trail systems could maximise health impacts by reaching greater population percentages. We assessed the temporal effects of linear greenspace exposure on health by examining the impact of the Bayou Greenways (BGs) linear trail implementation on health conditions and hospitalisations. We retrospectively analysed inpatient hospitalisation records for Harris County, Texas, from 2015–2019. Thirteen health conditions were explored with hospital admission rates per zip code as the primary outcome. Primary exposure variables were attributes of the BGs interconnected trail system: access duration, ten-minute walk proximity, and access point density. Models were evaluated to assess associations between admission rates in zip codes with and without BGs. Unadjusted analyses for zip codes with high access to trails had reduced odds of admission for obesity (OR, 95%CI: 0.18, 0.10–0.30), ischaemic heart disease (IHD; OR, 95%CI: 0.56, 0.34–0.93), and acute myocardial infarction (AMI; OR, 95%CI: 0.59, 0.37–0.94). Zip codes with >30% of the population within a ten-minute walk showed significant reduction in odds of hospital admission for obesity, (OR, 95%CI: 0.07, 0.03-0.17), IHD (OR, 95%CI: 0.23, 0.12–0.44), and AMI (OR, 95%CI: 0.29, 0.14–0.62). Analysis of socio-economic status (SES) demonstrated that low income and less densely populated areas showed increased admissions for obesity, IHD, AMI, and all-cause hospitalisations. Access to trails may be important in lower SES areas. These findings can inform public policy to integrate greenspace to support healthier communities.